Desensitization of Angiotensin II effect on [Ca2+]i, inositol triphosphate and prolactin in pituitary cells - González Iglesias, Arturo (2001)
Activation of pituitary angiotensin (ANG II) type 1 receptors (AT1) mobilizes intracellular Ca2+, resulting in increased prolactin secretion. We first assessed desensitization of AT1 receptors by testing ANG II-induced intracellular Ca2+ concentration ([Ca2+](i)) response in rat anterior pituitary cells. A period as short as 1 min with 10(-7) M ANG II was effective in producing desensitization (remaining response was 66.8 +/- 2.1% of nondesensitized cells). Desensitization was a concentration-related event (EC(50): 1.1 nM). Although partial recovery was obtained 15 min after removal of ANG II, full response could not be achieved even after 4 h (77.6 +/- 2.4%). Experiments with 5 x 10(-7) M ionomycin indicated that intracellular Ca2+ stores of desensitized cells had already recovered when desensitization was still significant. The thyrotropin-releasing hormone (TRH)-induced intracellular Ca2+ peak was attenuated in the ANG II-pretreated group. ANG II pretreatment also desensitized ANG II- and TRH-induced inositol phosphate generation (72.8 +/- 3.5 and 69.6 +/- 6.1%, respectively, for inositol triphosphate) and prolactin secretion (53.4 +/- 2.3 and 65.1 +/- 7.2%), effects independent of PKC activation. We conclude that, in pituitary cells, inositol triphosphate formation, [Ca2+](i) mobilization, and prolactin release in response to ANG II undergo rapid, long-lasting, homologous and heterologous desensitization.